Otimização de rotas tecnológicas de processamento e distribuição de resíduos municipais - Balcazar, Juan Galvarino Cerda [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
With the increase in population and industries, an increase in waste generation of various nature is observed. Domestic waste, industrial waste health service, among others, must be safely disposed. There are several ways to dispose the waste in a secure manner, such as controlled landfills, bio-digestion plants and incinerators, solutions that are used separately. By the other side, in recent decades a significant increase in power consumption was observed due to various factors, such as population growth and improved quality of life. In this research, an optimization model that encompasses the use of different technologies for energy generation and technological pathways for processing of waste through processes of thermal, biological and recyclable was analyzed. The model is applied in a case study for the metropolitan regions of São Paulo, Campinas and the Paraíba Valley and the North Coast just using consolidated technologies for waste processing. The results show a considerable production of electric energy even given to recycling and bio-stabilization. The heat treatment produces ash that can be used in industry or can be disposed of as landfill cover. The sale of raw materials produced by recycling and organic fertilizer technologies make this project financially attractive. The use of waste transportation improves efficiency, power generation and financial revenue. It also analyzes the advantages of a reduction in emissions of carbon equivalent, in which this difference can be commercialized. From the modeling performed, it was found that some regions should concentrate liquid and organic wastes to enhance the biogas generation in bio-stabilization waste technologies, enabling the increase of hybrid cycles, thereby improving the electric power processing plants. Electric energy, organic fertilizer, recycled matter and ash can be sold, ... (Complete abstract click eletronic access below)

Com o aumento da população e das indústrias houve um aumento na geração de resíduos de diversas origens. Os resíduos domésticos, industriais, resíduos de serviço de saúde, dentre outros, devem ser dispostos de forma segura. Existem diversas maneiras de disposição final segura para os resíduos, tais como aterros sanitários controlados, usinas de biodigestão e incineradores, soluções essas que são empregadas separadamente. Por outro lado, nas últimas décadas houve um aumento significativo no consumo de energia elétrica devido a diversos fatores, tais como o aumento populacional e a melhoria da qualidade de vida. Nesta pesquisa foi analisado um modelo de otimização que engloba o uso de diferentes tecnologias de geração de energia e rotas tecnológicas de processamento dos resíduos por meio de processos térmicos, biológicos e recicláveis. O modelo é aplicado em estudo de caso para as regiões Metropolitanas de São Paulo, Campinas, Vale do Paraíba e Litoral Norte, utilizando tecnologias consolidadas para processamento de resíduos. O tratamento térmico gera cinzas que podem ser utilizadas na indústria ou podem ser dispostas em aterros sanitários. O uso do transporte dos resíduos melhora a eficiência, geração de energia elétrica e a receita financeira. Analisa-se também a vantagem da redução das emissões de dióxido de carbono equivalente, sendo que esta diferença pode ser comercializada. A partir da modelagem realizada, verificou-se que algumas localidades devem concentrar os resíduos líquidos e orgânicos para aumentar a geração de biogás em tecnologias de bioestabilização, possibilitando o aumento de ciclos híbridos, consequentemente melhorando a potência elétrica das plantas de processamento. Nas plantas ocorre a venda de energia elétrica, adubo orgânico, materiais reciclados e cinzas, ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Resíduos sólidos; Sustentabilidade; Otimização matematica; Lógica difusa; Residuos - Subprodutos; Lixo - Eliminação; Reaproveitamento (Sobras, refugos, etc.); Biodigestor; Sustainability